Strategi Kepala Madrasah Dalam Meningkatkan Minat Masyarakat Terhadap Madrasah - Maryan Hasan; Siti Anisah; RA Mustika Hariyanti (Advances In Education Journal, 2025)
In present-day Indonesia, both Islamic and non-Islamic educational institutions have flourished, competing to educate their students and produce future generations that are exceptional and contributive to the nation. Madrasah educational institutions (MI and MTs) still face a shortage of students. This issue arises due to factors such as a lack of trust from parents in the institutions, insufficient engagement between teachers, headmasters, and the community, and an inability to effectively implement strategies that build community trust. This research aims to examine how the collaboration between madrasah heads and the community can advance education in madrasahs and how madrasah heads attract the interest of the community to enroll their children in madrasah. This study discusses madrasah leadership using a literature study method. The findings indicate that there is a strong relationship between madrasahs and the community in increasing the interest of the community to send their children to madrasah. Strategies that can be employed by madrasah heads include continuously building partnerships with the community, thus significantly increasing the acceptance of new students every year. Madrasah heads can attract the community's interest by implementing various strategies, such as engaging with the community, collaborating with other institutions, offering superior programs, and promoting the madrasah.